Static strength calculation of DN 350 branch pipe cutting-in in the main circulation pipeline of reactor plant WWER-1000; IOP Conference Series: Materials Science and Engineering; Vol. 487 : Technogenic Systems and Environmental Risk - Ovsenev A. E. Alexander Evgenievich; Pimenov N. O. Nikita Olegovich; Semenov A. O. Andrey Olegovich; Bibik I. S. Irina Sergeevna; Balachkov M. M. Maxim Mikhailovich (2019, 2019)
Title screen